Application of Mamdani's Fuzzy Logic in Determining the Price of Silk Fabric in Ujung Pandang District - Nuridayanti Nuridayanti; Raodatul Fadilah; Fahriansyah Fahriansyah (Journal of Renewable Energy and Smart Device, 2023)
The development of the silk textile industry in Indonesia is supported by several provinces including South Sulawesi. South Sulawesi has several centers for the development of mulberry and silkworm cultivation which are the basic ingredients for making silk cloth. Silk cloth is one of the processed products from silk thread which is produced from cocoons produced by silkworm cultivation and woven into silk cloth. Traditional woven fabrics produced in regions in Indonesia, including South Sulawesi, are not only made for clothing purposes. The purpose of this study is to determine the price of silk cloth by applying the Mamdani fuzzy method to the MATLAB software, so that silk cloth businesses can set prices according to the quality of the goods. Fuzzy logic is considered capable of mapping an input into an output without ignoring the existing factors. Based on this, fuzzy logic will produce a model of a system capable of estimating selling prices.